All Days 2009
DOI: 10.2118/128343-ms
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Nigerian Marginal Oil Fields - Identifying High Impact Variables

Abstract: Marginal Field Development in the prolific Niger Delta environment has taken on added significance since the Federal Government of Nigeria adopted an aggressive Reserve and Production Capacity development strategy as a launch pad for rapid economic development. The last few years have witnessed a number of developments in this area with the Government approving a new set of fiscal parameters for Marginal field development. Various strategies have been proposed to enhance the economic value from Marginal field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The economics of Marginal Field Development was investigated by Akinpelu and Omole in 2009, to determine the most important factors affecting the economy. The fiscal and regulatory terms of the NNPC for 2002 were used [61]. Because production typically dominates Nigerian Oil and Economic models, the production variable was treated as one of the main uncertain variables in the probabilistic model.…”
Section: Expected Net Present Value (Npv)mentioning
confidence: 99%
See 1 more Smart Citation
“…The economics of Marginal Field Development was investigated by Akinpelu and Omole in 2009, to determine the most important factors affecting the economy. The fiscal and regulatory terms of the NNPC for 2002 were used [61]. Because production typically dominates Nigerian Oil and Economic models, the production variable was treated as one of the main uncertain variables in the probabilistic model.…”
Section: Expected Net Present Value (Npv)mentioning
confidence: 99%
“…They suggested that future research should not restrict the variables to those that affect production and well costs. The cost management strategy should take into account additional expenses, such as investments in flow lines and jackets, barge costs, and operating expenses [61].…”
Section: Expected Net Present Value (Npv)mentioning
confidence: 99%
“…A field that may not produce enough net income to make it worth developing at a given time; should technical or economic conditions change, such a field may become commercial 21 . b. A field with estimated average production capacity not expected to exceed 10,000 bbl per day 1 . c. The Nigerian Department of Petroleum Resources classifies fields with the following characteristics as marginal 1 .…”
Section: Key Definitionsmentioning
confidence: 99%
“…Similar studies consist of [7][8][9][10]. Others are: [11][12]. Extensive literature exist on the various approaches to handling risks in projects but very few studies appear to have addressed risks in marginal oil fields.…”
Section: Introductionmentioning
confidence: 99%